Work-based-learning development in Latvia: success and further challenges by views of educators, employers and students - Buligina, Ilze; Sloka, Biruta (My University, 2020)
Latvia is among countries showing significant results in the introduction and implementation of work-based learning – being a country with historically school based vocational education and training system. The current research is devoted to the analysis of developments and challenges of work-based learning in Latvia - by views of entrepreneurs, educators and students. Research methods used were: scientific publications and previous conducted research analysis, analysis of survey results of entrepreneurs, educators and students on several aspects of work-based-learning. To have deeper analysis of specific aspects of work-based-learning the respondents were asked to evaluate the analysed aspects in scale 1 – 10, where 1 – do not agree and 10 – fully agree. In the implementation of the survey the Confederation of Employers of Latvia was involved. Survey data analysis methods were: descriptive statistics (indicators of central tendency or location – arithmetic mean, mode and median, indicators of variability – standard deviations, standard error of mean), cross-tabulations of evaluations by educators, entrepreneurs and students by their information level on entrepreneurship development possibilities in Latvia, testing of statistical hypotheses on differences of arithmetic means by t-test, by analysis of variance (ANOVA) for significance of evaluations’ differences regarding the received support for the implementation of work-based learning. Results of analysis has indicated that Latvia has made a significant progress and presents achievements in the education and training of qualified specialists, as well as is aware of challenges. This refers to several innovative approaches that could be applied to find best solutions for a successful implementation of work-based-learning for the preparation of qualified specialists for the economic development of Latvia.
Keywords: Educators; Employers; Public administration; Students; Work-based-learning; Research Subject Categories::SOCIAL SCIENCES::Social sciences